STUDY OF FAUZI CYCLE FOR HEAT ENGINE - PERDANA (NIM : 131 03 077); Pembimbing : Prof. Dr. Ir. T. A. Fauzi Soelaiman, MSME, BINEKA
Engine performance improvement could be done by changing and fixing its thermodynamic cycle. Fauzi says that there are possibilities to form new cycles form its thermodynamic processes, such isobaric, isochoric, isentropic, isenthalpic, and isothermal processes. As many as 34 from 102 Fauzi cycle sets are proposed to be heat engine cycle sets in this study. Those cycle sets then limited into several categories: (1) heat engine with maximum spesific work, (2) modified heat engines from general heat engine, and (3) heat engines that use waste heat. First, heat engine with maximum spesific work is a heat engine with rectangle form in pressure-specific volume diagram. Second, modified heat engines are general heat engines that change their isentropic compression to isothermal compression in order to reduce back-work ratio and use heat regeneration to increase the efficiency. These heat engines have higher efficiency at lower compression ratio or pressure ratio and lower back work ratio except modified Diesel heat engine that has higher back work ratio. Third, heat engines that use waste heat are heat engines that are capable to extract heat until temperature close to sourrounding temperature. With heat regeneration, Fauzi heat engines in this study have several superiorities such as higher efficiency and/or lower back-work ratio than general heat engines.